Videofeedback e vídeomodelação aplicados à Intervenção Mediada por Pares para o ensino de habilidades acadêmicas a crianças com Transtorno do Espectro Autista - Degen, Krislainy Souza (2025)
Studies have shown that peer-mediated teaching methods, such as Peer-Mediated Intervention (PMI), have been shown to be effective in promoting academic skills in children with neurodevelopmental disorders. However, the use of several training components in the same procedure has made it difficult to identify which element is most effective for peer training. This study aimed to investigate which of two video techniques for teaching behaviors (videofeedback or videomodeling) would demonstrate better results in promoting peermediated skills for teaching academic skills in children with Autism Spectrum Disorder (ASD) in a PMI program and its effects on the performance of children with ASD. The study followed an experimental design of Alternating Treatments, involving three dyads composed of a child with ASD and a peer child, aged between six and nine years. The sessions took place in two public schools and included phases of Pre-Test, Baseline, Alternating Treatment, Extended Treatment, Generalization, Follow-up and Social Validity. The results indicated that the videomodeling component was more efficient in teaching the mediating behaviors to the three peers. However, the effects on the responses of children with ASD varied between the dyads. Some variables that have been shown to interfere in the acquisition of responses by children with ASD were discussed. The Social Validity data indicated a general acceptance of the intervention. Suggestions for future studies focusing on academic content and involving more participants were made